HAKIKAT BAHASA, NASIONALISME, DAN JATIDIRI BANGSA DALAM KEBIJAKAN PENDIDIKAN BAHASA - Sukarno Sukarno (EDUKASI, 2021)
Indonesia as a large archipelagic country causes Indonesia to have the largest number of regional languages in the world. Each region has its own regional language, so for the purposes of communication that unites the nation, a unified language is needed, Indonesian. Meanwhile, for the purposes of international relations, foreign languages, especially English, are vital. Thus, languages in Indonesia are categorized into regional languages, national languages, and foreign languages. As a means of communication, the language used reflects the function and character of the speaker. This paper discusses the nature of language, nationalism, national identity in language education policy.